Examination of attitudes of students of biomedical sciences towards the applicability of social media in communication with patients - Krajnović, Dušanka; Milošević-Georgiev, Andrijana; Rajić, Kristina; Šesto, Sofija; Stević, Ivana (Archives of Pharmacy, 2022)
Technology development, higher Internet and smart devices accessibility have contributed to increasing the use and application of social media, online platforms and applications in healthcare, where healthcare professionals use social media both privately and while performing professional tasks. The aim of the research was to examine attitudes of biomedical sciences students towards application of social media in communication with patients. A questionnaire was created, then distributed using the Snowball technique. 311 students participated, all of whom used social media at least once. YouTube, Instagram, and Facebook are the most used platforms, used daily (97.11%) for personal and/or professional use. 82.24% believe helping patients to understand online information is a new pharmacists' duty in digital age, and 61.09% that it is their obligation to keep up with current trends in social media usage. The majority thinks that social media have the potential to improve communication between pharmacists and patients (76.38%) and that it is ethically acceptable for pharmacists to communicate with patients through social media (55.63%), without violating their confidentiality (53,23%). Every second student thinks that it is ethically unacceptable for a pharmacist to communicate with a patient through social media private accounts, and to visit patients' profiles (51.77%). Encouraging is that 92.60% find it unacceptable that patients' confidential information is shared without patients' consent. The results indicate a positive attitude of biomedical sciences students about using social media to help patients understand information available online, and that social media have the potential to improve communication between pharmacists and patients.